Bipolar Junction Transistor 1/f Noise Simulation and Parameter Extraction Technique - Zeltins, M.; Slaidins, I. (Elektronika ir Elektrotechnika, 2005)
In many cases it is important for practical applications to determine 1/f noise parameters of BJT for SPICE model but their exact values could not be theoretically predicted and must be obtained from the measurements. In this paper error sources in determination of noise parameters from measurement data are discussed. Different bipolar junction transistor noise measurement circuits are analysed using simulation technique to determine the most favourable circuit configuration and bias conditions. Some specific cases and problems related to noise parameter extraction are discussed. Ill. 8, bibl. 8 (in English; summaries in Lithuanian, English and Russian).